Victorians on Broadway : literature, adaptation, and the modern American musical - Weltman, Sharon Aronofsky, 1957- (University of Virginia Press, 2020)
"Victorians on Broadway" is a wide-ranging interdisciplinary study of live stage musicals from the mid- to late twentieth century adapted from British literature written between 1837 and 1886. Investigating musical dramatizations of works by Charles Dickens, Charlotte Brontë, Christina Rossetti, Robert Louis Stevenson, and others, Weltman considers what cultural and interpretive work adaptations such as "The King and I" (1951), "Oliver!" (1960), "Sweeney Todd" (1979), and "Jekyll and Hyde" (1997) accomplish when they are adapted for the Broadway stage. In addition, Weltman examines what these musicals teach us about the Victorian books from which they derive. "Victorians on Broadway" also provides us with a great deal of background theater history, making sure that we can understand how "the American musical" developed its own generic specificity. The book moves chronologically, reflecting the major developments in American musical theater, and Victorian-sourced Broadway musical adaptations have been produced at each stage: the Golden Age of Broadway, the musical theater experiments of the 1970s and 1980s that focus as much on concept as story (exemplified by Stephen Sondheim), and the era of pop megamusicals, revealing the Broadway musical's debt to melodrama. Organizing these chapters chronologically situates the adaptations within the history of musical theater and focuses attention on how they fit into aesthetic and intellectual movements"-- Provided by publisher.
Keywords: Musicals -- United States -- 20th century -- History and criticism.; Musical theater -- United States -- History -- 20th century.; English literature -- 19th century -- Influence.; Musicals -- Stories, plots, etc.; Théâtre musical -- États-Unis -- Histoire -- 20e siècle.; Littérature anglaise -- 19e siècle -- Influence.; LITERARY CRITICISM -- American -- General.; English literature -- Influence; Musical theater; Musicals; United States; 1800-1999; Criticism, interpretation, etc.; History; Stories, plots, etc.